Juice and Wine Quality Responses of Vitis vinifera L. cvs. Sauvignon blanc and Chenin blanc to Timing of Irrigation during Berry Ripening in the Coastal Region of South Africa - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
The effects of additional irrigation during berry ripening on juice and wine quality in Sauvignon blanc and Chenin blanc grapevines were investigated. In all treatments the grapevines were irrigated when berries reached pea size in December. One treatment received no further irrigation until after harvest. All of the remaining treatments received a second irrigation at véraison. Except for a single treatment, which was not irrigated during ripening, these treatments received a third irrigation either 14, 21, 28 or 31 days after véraison. The six treatments were applied in a field trial carried out in the Stellenbosch district of the Coastal winegrowing region of South Africa over consecutive seasons, between 1990 and 1993. Irrigation during berry ripening decreased the N concentration in the juice of both cultivars, but increased the P and Ca concentrations in the juice, though only in Sauvignon blanc. In neither cultivar were the juice K and Mg concentrations affected by irrigation during the ripening period. The irrigation treatments did not affect sugar concentration in Sauvignon blanc grapes. In contrast, sugar concentrations in Chenin blanc grapes that were irrigated 28 days after véraison were lower than in grapes that were irrigated at pea size. Irrigation applied 21 days and 28 days after véraison resulted in higher total titratable acidity in the juice of both cultivars. Irrigation applied 31 days after véraison, i.e. three days before harvest, raised juice pH in Chenin blanc grapes relative to grapevines that received a single irrigation at pea size. Although not consistent over seasons, irrigation applied during the later stages of ripening had negative effects on fresh vegetative aroma (green pepper, herbaceous or green cut grass flavours) and fullness of Sauvignon blanc wines. Similarly, irrigation during the middle stages of ripening reduced the fermentation character (guava flavour) and fullness of Chenin blanc wines, though not in all seasons. Overall, irrigation during berry ripening tended to reduce wine quality in both cultivars.